2017
DOI: 10.3846/13923730.2017.1319413
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of flexural behaviour of layered steel fibre reinforced concrete beams

Abstract: The building of structures from steel fibre reinforced concrete (SFRC) in the external and conventional reinforced concrete (RC) in the internal layer represents an economical alternative of structures effectively using SFRC. The paper presents test results of flexural behaviour of layered beams with SFRC external layers and RC internal layer. The behaviour of these beams is compared to test results of SFRC and conventional RC beams. The test results show, that the flexural load capacity for all series of beam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…29 Although their flexural load capacities are approximately similar, the deflection of a layered section is reduced when compared with that of a monolithic section. 30 The finite element method (FEM) is regarded as one of the most popular numerical methods for investigation of crack growth and coalescence. 31 Use of a lightweight aggregate fibrous concrete bottom layer with a normal-density concrete topping layer in two-layered beams reduced the beam weight by 42% when compared with a single-layered beam formed using normal-density concrete with similar bending resistance.…”
Section: Introductionmentioning
confidence: 99%
“…29 Although their flexural load capacities are approximately similar, the deflection of a layered section is reduced when compared with that of a monolithic section. 30 The finite element method (FEM) is regarded as one of the most popular numerical methods for investigation of crack growth and coalescence. 31 Use of a lightweight aggregate fibrous concrete bottom layer with a normal-density concrete topping layer in two-layered beams reduced the beam weight by 42% when compared with a single-layered beam formed using normal-density concrete with similar bending resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Guo Zan [16] established an experimental model for internal cracks in layered steel fiber-reinforced concrete and hybrid steel fiber-reinforced concrete and obtained the relationship curve between load and crack development. Peng O [17] and foreign scholar Inmaculada Martínez-Pérez et al [18] compared the mechanical properties of layered steel fiber-reinforced concrete beams, steel fiber-reinforced concrete beams, and ordinary concrete beams. The study showed that the bending capacity of each beam is basically the same, and the deflection of the LSFRC beam is slightly smaller than that of the solid beam.…”
Section: Introductionmentioning
confidence: 99%
“…When UHPC in the high-stress zone fails under load, UHPC in the low-stress zone does not fully play its role (Ge et al, 2019; Zhang et al, 2014). To make more effective use of UHPC and reduce resource consumption, the wet joint structure of the precast bridge deck needs to be optimized (Cao et al, 2019; Martinez-perez et al, 2017). Therefore, the design concept of a functional gradient structure (Gao and Ma, 2009; Li and Xu, 2009; Wen et al, 2010) was introduced to replace the NC in the negative moment area of the wet joint area with UHPC to form the wet joint structure form of upper-layer NC and lower-layer UHPC.…”
Section: Introductionmentioning
confidence: 99%